2007
DOI: 10.1051/0004-6361:20078420
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of C IV pumped fluorescence of Fe II in symbiotic stars

Abstract: Aims. We describe how the C iv λ1548.18 line pumps the 1548.20 and 1548.41 Å channels of Fe ii in symbiotic stars through the process known as photo-ionization by accidental resonance (PAR). We describe where and why Fe ii fluorescence arises in symbiotic stars and whether the Fe ii λ1548.41 channel can only be activated when there is a white-dwarf wind present in the system. Further, we aim to show how an analysis of the PAR-pumped lines helps to understand the phyisical conditions that they manifest.Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The expansion velocity of the nova as computed by Thackeray (1977) gives a radius of ∼670 AU for the nebula in rough agreement with a distance of a few kpc. Eriksson et al (2008) found that the Fe ii fluorescence nebula has a mean radius of 450 ± 50 AU. Munari & Whitelock (1989) noted that among all the well-studied D-symbiotics, RR Tel was the only one that had not been observed to undergo a dust obscuration event.…”
Section: The Mira and The Hot Starmentioning
confidence: 99%
“…The expansion velocity of the nova as computed by Thackeray (1977) gives a radius of ∼670 AU for the nebula in rough agreement with a distance of a few kpc. Eriksson et al (2008) found that the Fe ii fluorescence nebula has a mean radius of 450 ± 50 AU. Munari & Whitelock (1989) noted that among all the well-studied D-symbiotics, RR Tel was the only one that had not been observed to undergo a dust obscuration event.…”
Section: The Mira and The Hot Starmentioning
confidence: 99%
“…Another mechanism, known to occur in spectra of circumstellar envelopes of symbiotic stars and in the environs of gamma-ray bursts is Bowen fluorescence of Fe ii by C iv emission at 1548 Å (e.g. Johansson 1983;Eriksson et al 2008;Vreeswijk et al 2007;Hartman & Johansson 2000;Michalitsianos et al 1992). Pumping occurs as the 1548.19 Å resonance line of C iv closely coincides with the 1548.20 Å transition from the a 4 F 9/2 metastable level to the y 4 H o 11/2 level of Fe ii.…”
Section: Electron Density Determinationmentioning
confidence: 99%
“…Therefore, an overabundance of iron cannot help to explain the Fe ii emission by a photoionization model, but the Fe ii region should be heated by an additional mechanism; that is, the Fe ii spectrum is not produced directly by photoionization but more probably by shocks. Indeed, it is generally believed that collisional excitation is responsible for the bulk of the Fe ii emission, and it has been shown how these lines may represent, especially in SSs, one of the most direct traces of fast outflows of WD winds (Eriksson, Veenhuizen & Nilsson 2007). Inelastic collisions with electrons excite the odd parity levels near 5 eV which then decay into the optical and UV lines.…”
Section: The 1962 Spectrummentioning
confidence: 99%
“…but more probably by shocks. Indeed, it is generally believed that collisional excitation is responsible for the bulk of the FeII emission, and it has been shown how these lines may represent, especially in SSs, one of the most direct traces of fast outflows of WD winds (Eriksson et al 2007). Inelastic collisions with electrons excite the odd parity levels near 5 eV which then decay into the optical and UV lines.…”
Section: The Feii Linesmentioning
confidence: 99%